Moisture resistance evaluation on single electronic package moulding compound. Issue 6 (29th November 2019) - Tan, Cher Ming; Narula, Udit; Seow, Guan Ling; Sangwan, Vivek; Chen, Ching Hsiang; Lin, Shu Ping; Chen, Jia Yuan
Abstract : Non-destructive evaluation indices that correlate with the moisture resistance of integrated circuit packages are developed. Abstract : Non-destructive evaluation indices that correlate with the moisture resistance of integrated circuit packages are developed. These indices are developed from detailed studies on the functional groups in a moulding compound, and their effectiveness is verified experimentally. With these indices, one can ensure the moisture resistance of an individual package without the need of the standard humidity tests which require long test durations on limited number of samples where extrapolation with statistical uncertainty will be present.